Discovery and preclinical development of a therapeutically active nanobody-based chimeric antigen receptor targeting human CD22 - McComb, Scott; Arbabi-Ghahroudi, Mehdi; Hay, Kevin A.; Keller, Brian A.; Faulkes, Sharlene; Rutherford, Michael; Nguyen, Tina; Shepherd, Alex; Wu, Cunle; Marcil, Anne; Aubry, Annie; Hussack, Greg; et al. (Molecular Therapy: Oncology, 2024)
Chimeric antigen receptor (CAR) T cell therapies targeting B cell-restricted antigens CD19, CD20, or CD22 can produce potent clinical responses for some B cell malignancies, but relapse remains common. Camelid single-domain antibodies (sdAbs or nanobodies) are smaller, simpler, and easier to recombine than single-chain variable fragments (scFvs) used in most CARs, but fewer sdAb-CARs have been reported. Thus, we sought to identify a therapeutically active sdAb-CAR targeting human CD22. Immunization of an adult Llama glama with CD22 protein, sdAb-cDNA library construction, and phage panning yielded >20 sdAbs with diverse epitope and binding properties. Expressing CD22-sdAb-CAR in Jurkat cells drove varying CD22-specific reactivity not correlated with antibody affinity. Changing CD28- to CD8-transmembrane design increased CAR persistence and expression in vitro. CD22-sdAb-CAR candidates showed similar CD22-dependent CAR-T expansion in vitro, although only membrane-proximal epitope targeting CD22-sdAb-CARs activated direct cytolytic killing and extended survival in a lymphoma xenograft model. Based on enhanced survival in blinded xenograft studies, a lead CD22sdCAR-T was selected, achieving comparable complete responses to a benchmark short linker m971-scFv CAR-T in high-dose experiments. Finally, immunohistochemistry and flow cytometry confirm tissue and cellular-level specificity of the lead CD22-sdAb. This presents a complete report on preclinical development of a novel CD22sdCAR therapeutic. [Display omitted] McComb and colleagues report on their work to develop a camelid-nanobody-based chimeric antigen receptor-T cell therapy targeting human CD22 antigen. A membrane-proximal domain targeting CD22 nanobody CAR incorporating a CD8-transmembrane domain was selected as lead based on superior in vitro cytotoxicity, specificity, persistence, and in vivo activity.